Proceedings of the 3rd International Conference on Banking, Accounting, Management and Economics (ICOBAME 2020) 2020
DOI: 10.2991/aebmr.k.210311.008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Budget Participation on Managerial Performance with Organizational Commitment and Motivation as Moderating Variables (Empirical Study at the Local Government Work Unit Office of Ende Regency)

Abstract: This study aims to show whether there is an influence between budgetary participation and managerial performance where organizational commitment and work motivation are moderating variables in the Regional Office of Work Units (SKPD), Ende District, NTT. The existence of differences in the results of previous studies motivated researchers to see whether the findings made by previous researchers gave the same or different results when carried out in different locations. Data was collected by distributing questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(13 reference statements)
3
5
0
Order By: Relevance
“…This illustrates that an increase in management efficiency is influenced by participation in the budgeting itself and that participation is correlated with an increase in management efficiency. In line with the research, it can be seen from the previous description that managerial performance increases when participation in budgeting increases (Maulida et al, 2021;Soleiman & Thalib, 2021).…”
Section: The Effect Of Budget Participation On Managerial Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…This illustrates that an increase in management efficiency is influenced by participation in the budgeting itself and that participation is correlated with an increase in management efficiency. In line with the research, it can be seen from the previous description that managerial performance increases when participation in budgeting increases (Maulida et al, 2021;Soleiman & Thalib, 2021).…”
Section: The Effect Of Budget Participation On Managerial Performancesupporting
confidence: 87%
“…This research is in line with the conclusions that managerial performance is not affected by the clarity of budget objectives. Managerial performance is affected by the clarity of budget objectives (Maulida et al, 2021;Soleiman & Thalib, 2021). The Sig value based on the results of the F test is 0.000 <0.05, or the value of Fcount > Ftable is 29.545 > 3.25, indicating that Ha is accepted and H0 is rejected.…”
Section: The Effect Of Budgetary Target Clarity On Managerial Perform...mentioning
confidence: 99%
“…In line with the research conducted by Pakpahan et al (2018), it shows that the organizational commitment factors moderate the connection between budgetary involvement and management performance. However, Soleiman & Thalib (2021) and Suardana & Suryanawa (2010) found that organizational commitment cannot modify the association between budgetary involvement and management performance.…”
Section: Template Of Jurnal Economiamentioning
confidence: 97%
“…Although previous research results are partially still very limited (decentralization and budgetary participation), inconsistent (budgetary participation and managerial performance), and consistently positive (decentralization and managerial performance), the literature review results show that research on decentralization and budgetary participation has only been studied by Riyadi (2007). Furthermore, the results of research between budgetary participation and managerial performance have significant positive results (Purwanti et al, 2017;Soleiman & Thalib, 2020;Pradana, 2021;Hussein et al, 2021), negative significant (Bryan & Locke, 1967) and insignificant (Candrakusuma & Jatmiko, 2017;Kahar et al, 2019;Firana, 2020). Consistently, there is a significant positive relationship between decentralization and managerial performance (Purwanti et al, 2017;Amran, 2020).…”
Section: Introductionmentioning
confidence: 92%
“…Decentralized power sharing allows managers to have the opportunity to actively participate in the budgeting process which in turn will provide motivational support to subordinates to improve their performance (Firmansyah & Mahardhika, 2018). The results also show that decentralization has a significant positive effect on managerial performance (Purwanti et al, 2017;Soleiman & Thalib, 2020;Amran, 2020). For this reason, the proposed hypothesis is formulated: H 1 : Decentralization has a positive effect on managerial performance Dakhli (2021) shows that managers or subordinates in decentralized organizations feel themselves to be more influential people, participate more in budget planning, and feel satisfied with budgetrelated activities.…”
Section: Introductionmentioning
confidence: 99%